Patterns of multiple intelligences and their relationship to achievement in mentally gifted students A study of students of excellence in Damascus - Zahlok, Maha; Adam, bsmaa; Saleh, Weeam (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The study aimed to study the patterns of multiple intelligences and their relation to the achievement of high-school students in the high school and to identify the types of multiple intelligences most common among the outstanding students in the research sample. The researcher followed the analytical descriptive method. The sample consisted of (72) male and female students The study tools consisted of the MIDAS scale for multiple intelligences. The researcher conducted the statistical analysis necessary to confirm the psychometric properties of the research tools and to verify the validity of the hypotheses. The results were as follows: 1. Logical intelligence was ranked first among high school students who excelled in the research sample followed by social and linguistic intelligence. 2.There are no statistically significant differences between the average grades of high school students of the high achievers on the multiple intelligences scale due to the academic achievement variable. 3.There are statistically significant differences between the average grade of high school students on the multiple intelligence scale due to the gender variable on logical intelligence in favor of males and social intelligence in favor of females. Based on the results of the study, the researcher recommends the need to conduct more research and field studies on multiple intelligences and achievement in primary or other educational stages, and a comparison between the outstanding and ordinary secondary students or other stages of education in multiple intelligences. And conduct research and studies to reveal the relationship between multiple intelligences and other variables.